SMARCA4‐deficient undifferentiated tumor that responded to chemotherapy in combination with immune checkpoint inhibitors: A case report. Issue 15 (2nd July 2022) - Utsumi, Takahiro; Taniguchi, Yohei; Noda, Yuri; Fukai, Mari; Kibata, Kayoko; Murakawa, Tomohiro
Abstract: Thoracic SMARCA4‐deficient undifferentiated tumors are a new type of neoplasm that commonly occur in the mediastinum, progress rapidly, and show a poorer prognosis. We report a case of thoracic SMARCA4‐deficient undifferentiated tumor in the right thoracic cavity in a patient with a history of heavy smoking and presenting with respiratory distress and hemoptysis. Imaging showed pleural effusion and thickening. A diagnostic right pleural biopsy yielded multiple white nodules and pale bloody pleural effusion accumulated in the right thoracic cavity. Histopathologically, the tumor cells were large, some exhibited rhabdoid cytology, and they were surrounded by an infiltration of inflammatory cells. These tumor cells were negative for SMARCA4, p40, NUT, and claudin‐4, leading to establishing a diagnosis of thoracic SMARCA4‐deficient undifferentiated malignancy. We treated the patient with atezolizumab, carboplatin, and nab‐paclitaxel. The patient achieved stable disease at 7 months during this study. Although there is no standard treatment of this disease, our reported treatment may contribute to improved prognosis, requiring further research. Abstract : Thoracic SMARCA4‐deficient undifferentiated tumors are a new type of neoplasm that commonly occur in the mediastinum and are associated with poor prognosis. To date, there is no standard treatment of thoracic SMARCA4‐deficient undifferentiated tumors. We report a case of thoracic SMARCA4‐deficient undifferentiated tumor with hemoptysis. We treated the patient with atezolizumab, carboplatin, and nab‐paclitaxel, which resulted in achieving stable disease for 7 months. Our reported treatment may contribute to improved prognosis, which requires further evaluation.